Watershed Management and ‘Ecotonal Networks’. A Holistic Approach to Coastal Management - Polgar, Gianluca (Malaysian Journal of Science, 2013)
For the fi rst time in the history of our species, the opportunity of halting the expansion of our global population discloses future scenarios of stably coexisting urbanised and non-urbanised ecosystems. The need for the establishment of such scenarios is particularly urgent in tropical regions, whose higher biodiversity is being rapidly eroded by recent and explosive urbanisation and land conversion. It is here proposed that the sustainable management of networks of urbanised and non-urbanised systems, the latter ones being interconnected by transitional systems, or ecotones, is the key to manage increasingly fragmented and isolated natural systems. In a cybernetic perspective, a decrease in internal connectivity both modifi es fl uxes with the external environment and impairs negative feedbacks, thus decreasing ecosystems’ resilience. In particular, conservation efforts focused on traditionally conceived ecosystems have shown to be inappropriate to effi ciently manage and protect tropical coastal systems. All these ‘systems’, although being anthropomorphically perceived as separate, evolved as deeply interconnected networks. The increasing loss of biocomplexity and resilience faced by such networks, is the inevitable consequence of the loss of internal connectivity determined by the loss of ecotones, due to fragmentation, degradation, and anthropogenic impact acting on the periphery of isolated natural areas. In order to sustainably manage natural isolated systems surrounded by urban, agricultural or degraded systems, appropriate management of ecological inputs and outputs, and maintenance of internal connectivity should be urgently implemented. Ecosystem-based management offers a rational perspective: (i) maximising the diversity of the managed systems within the original landscape, and (ii) creating and managing a dynamic network of ecotonal connections maintaining fl uxes of energy and matter between them (Ecotonal NeTworks, or ENTs). Being inherently more resilient, such managed networks of natural subsystems would provide more sustainable and richer economic and ecological services, allowing for a rational integration of the highly interconnected urban subsystems. (Keywords: conservation, ecosystem management, resilience, sustainability, coastal management)